KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP NU SUNAN AMPEL DALAM MENYELESAIKAN MASALAH KONTEKSTUAL GEOMETRI [MATHEMATICS REPRESENTATION ABILITY OF NU SUNAN AMPEL JUNIOR HIGH SCHOOL STUDENTS IN SOLVING GEOMETRY CONTEXTUAL PROBLEMS] - Handayani, Ucik Fitri (JOHME: Journal of Holistic Mathematics Education, 2022)
The ability of mathematical representation is needed by students to communicate mathematical ideas. However, the student's representation ability is still not optimal, especially in geometry material. The purpose of this study is to describe the representational abilities of students of SMP NU Sunan Ampel in solving geometrical contextual problems. The study was conducted on 19 students at SMP NU Sunan Ampel Poncokusumo. Data was collected through tests and interviews. The indicators of representation ability used are visual representation, symbolic, and verbal. The results of the research are the level of student representation ability as much as 53% in the low category, as much as 42% in the medium category, and as much as 5% in the high category. Students with high representation ability can fulfill the indicators of visual, symbolic, and verbal representation well according to their abilities. Students with moderate representational abilities can meet the indicators of symbolic representation, but there are still errors in writing and calculations. Students with low representation ability have not reached the three indicators of representational ability well as a whole according to their abilities. It is hoped that the teacher can provide practice questions to students by requiring students to describe and write down the mathematical model in detail and completely. In addition, the teacher can also introduce various forms of flat shapes in contextual problems so that students can be trained to solve contextual problems related to flat shapes.BAHASA INDONESIA ABSTRACT: Kemampuan representasi matematika sangatlah dibutuhkan oleh siswa untuk mengkomunikasikan ide matematika. Namun, kemampuan representasi siswa masih belum optimal khususnya pada materi geometri. Tujuan penelitan ini mendeksripsikan kemampuan representasi siswa SMP NU Sunan Ampel dalam menyelesaikan masalah kontekstual geometri. Penelitian dilaksanakan pada 19 siswa di SMP NU Sunan Ampel Poncokusumo. Data dikumpulkan melalui tes dan wawancara. Indikator kemampuan representasi yakni representasi visual, simbolik, dan verbal. Hasil penelitian yakni tingkat kemampuan representasi siswa sebanyak 53% pada kategori rendah, sebanyak 42% pada kategori sedang, dan sebanyak 5% pada kategori tinggi. Siswa kemampuan representasi tinggi dapat memenuhi indikator representasi visual, simbolik, dan verbal dengan baik sesuai kemampuannya. Siswa kemampuan representasi sedang dapat memenuhi indikator representasi simbolik, namun masih terdapat kesalahan penulisan dan perhitungan. Siswa kemampuan representasi rendah belum mencapai ketiga indikator kemampuan representasi dengan baik secara keseluruhan sesuai dengan kemampuannya. Harapannya guru dapat memberikan latihan soal kepada siswa dengan mewajibkan siswa menggambarkan dan menuliskan model matematikanya secara detail dan lengkap. Selain itu, guru juga dapat memperkenalkan berbagai bentuk bangun datar dalam masalah kontekstual agar siswa dapat terlatih menyelesaikan masalah kontekstual yang berkaitan dengan bangun datar.